2023
DOI: 10.1088/1755-1315/1225/1/012026
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth, Yield and some Qualities Characteristics of Two Cherry Tomato (Solanum lycopersicum var. cerasiforme) Cultivars under Plastichouse Conditions

Mahmood A. R. Alani,
Ekhlas A. J. Elkaaby,
Wathiq A. Abdul Majeed
et al.

Abstract: The study was conducted to evaluate growth, yield and some qualities traits of two cherry tomato cultivars, Gardeners Delight and Golden Sunrise during the year 2017-2018. The experiment was designed in Completely Randomized Block Design (RCBD) with three replications. Results revealed that Gardeners Delight showed the highest plant height (198.33 cm), number of nodes (38 nodes.plant-1). and no significant differences were found in chlorophyll content in leaves for both cherry cultivars. Concerning to yield tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
1
0
0
Order By: Relevance
“…The recorded average temperature during the winter season was in the range of 23.85°C to 32.37°C. Consistent with the present results, a study reported plant heights of 198.33 cm and 172.33 cm, respectively, in two cherry tomatoes [42]. We found the increase in the total number of leaves remained constant until the last day of observation.…”
Section: Discussionsupporting
confidence: 93%
“…The recorded average temperature during the winter season was in the range of 23.85°C to 32.37°C. Consistent with the present results, a study reported plant heights of 198.33 cm and 172.33 cm, respectively, in two cherry tomatoes [42]. We found the increase in the total number of leaves remained constant until the last day of observation.…”
Section: Discussionsupporting
confidence: 93%